Resentment against the rich: Conceptualization, measurement, and empirical evidence from China. Issue 4 (28th May 2018) - Wu, Xiaoyi; Lin, Lan
Abstract : Purpose: Because of increasing wealth inequality, China has been confronted with resentment against the rich (referred to hereafter as RAR or Choufu in Chinese), which is a growing concern owing to its potential to foment social conflict. Drawing on social comparison and deonance theories, this paper aims to provide theoretical insights into RAR within the Chinese context and to develop an RAR scale. Following spillover theory, the attitudinal and behavioral outcomes of RAR in organizational settings will be explored. Design/methodology/approach: This research consists of two studies. Study 1 conceptualizes RAR and develops an RAR scale by using three separate samples. Exploratory and confirmatory factor analyses are conducted to establish scale reliability and validity. Study 2 uses hierarchical linear regression analysis to test whether employees' RAR attitude spills over from the societal to the organizational setting. Findings: Results suggest that RAR can be conceptualized as two distinct but related dimensions – emotional RAR and moral RAR. These two forms spill over to the workplace, influencing employees' work attitudes and behaviors. Emotional RAR relates negatively to life satisfaction and prosocial organizational behaviors and positively to unethical organizational behaviors. Moral RAR relates negatively to pay satisfaction and positively to prosocial behaviors. Practical implications: This research suggests that RAR has spillover effects from societal to organizational settings and demonstrates that a more robust understanding of employees' workplace experience requires acknowledging social experiences, such as conflicts beyond the workplace. Originality/value: This research contributes to the conflict management literature by exploring RAR as a negative attitude that serves to potentially ignite social conflict. It not only develops a theory-grounded, conceptual RAR model and a reliable RAR scale but also for the first time explores RAR attitudinal and behavioral outcomes beyond the social domain. This study serves as a meaningful touchstone for future research to incorporate social attitudes into organizational behavior research.